Discovery the intersection of performing arts in cultural tourism: a scoping review - Chamil Arkhasa Nikko Mazlan; Mohd Hassan Abdullah; Nor Shuradi Nor Hashim; Nurulakmal Abdul Wahid; Amsalib Pisali; Aiman Ikram Uyub; Norzuraina Mohd Nor; Riyan Hidayatullah (Discover Sustainability)
Abstract This study explores the intersection of performing arts and cultural tourism, identifying key trends and research gaps through a scoping review with selected bibliometric components. The analysis examines publication trends and citation metrics from 11 documents sourced from the Scopus database, using bibliometric analysis software, biblioMagika® version 2.9. The research reveals key themes, including the relationship between culture and tourism, the role of technology, such as augmented reality, in enhancing heritage experiences, and the preservation of local traditions amid tourism pressures. The study highlights that the role of performing arts in promoting sustainable tourism practices remains underexplored. The findings emphasize the need for a multidisciplinary approach and propose integrating performing arts more effectively into cultural tourism policies and practices. This study provides a foundation for future research aimed at enhancing sustainable tourism and expanding the geographical and cultural scope of analysis to include underrepresented regions.